Evaluating the effectiveness of a mental health literacy module - A randomized controlled trial among school teachers - Vidya Prabhu; Lena Ashok; Veena Ganesh Kamath; Amitha Puranik; Sebastian Padickaparambil; Nikitha Sibil Rebello; Praveen Arhanthabailu; Varalakshmi Chandrasekaran (Clinical Epidemiology and Global Health)
Objective: Teachers can greatly aid the promotion of adolescent mental health. Early intervention is key in reducing morbidity related to mental health conditions among adolescents. This study was undertaken to test the effectiveness of the MHL module among high school teachers. Methods: A parallel stratified cluster randomized controlled trial was conducted among high school teachers between November 2019 to September 2021. Schools were stratified based on the type of school and then randomized. Teachers from 29 schools received intervention and 28 schools were waitlisted and given intervention at the end of the trial. The effectiveness of the module was assessed using a baseline, post-test, and follow-up questionnaire. Repeated measures ANOVA adjusted for cluster effect was used to assess the change in knowledge, management, attitudes and beliefs over time in the intervention arm. Results: Significant improvement was observed in the intervention arm as compared to the control arm across the domains of knowledge and attitudes and beliefs with an increase in mean knowledge score of 3.34 (95 % CI: 2.14 to 4.55 p < 0.001) and an increase in mean attitudes and beliefs score of 0.95 (95 % CI: 0.42 to 1.49 p < 0.001). Conclusion: The present study found that the intervention module was effective in enhancing the MHL of teachers across all the domains, which may facilitate early intervention among adolescents at the school level.The trial has been registered with the Clinical Trials Registry of India prospectively. (CTRI/2017/11/010633)